Genotypes of Japanese encephalitis virus isolated in three states in Malaysia - Tsuchie, Hideaki; Oda, Kazumasa; Vythilingam, Indra; Thayan, Ravindran; Vijayamalar, Balasubramaniam; Sinniah, Mangalam; Singh, Jasbir; Wada, Takashi; Tanaka, Hiroshi; Kurimura, Takashi; Igarashi, Akira (American Society of Tropical Medicine and Hygiene, 1997)
Two hundred forty nucleotides from the pre-membrane gene region of 12 Japanese encephalitis virus (JEV) strains isolated from three different regions of Malaysia from 1993 to 1994 were sequenced and compared with each other and with the JEV strains from different geographic areas in Asia. These 12 Malaysian isolates were classified into two genotypes. The four JEV strains isolated from Sarawak in 1994 and the four JEV strains isolated from Sepang, Selangor in 1993 were classified into one genotype that included earlier isolated strains from Malaysia (JE-827 from Sarawak in 1968 and WTP/70/22 from Kuala Lumpur in 1970). The four JEV strains from Ipoh, Perak in 1994 were classified into another genotype that included JEV strains isolated from northern Thailand and Cambodia. In an earlier report, 10 JEV strains from Sabak Bernam, Selangor in 1992 were classified into the largest genotype that included strains isolated in temperate regions such as Japan, China, and Taiwan. The data indicate that at least three genotypes of JEV have been circulating in Malaysia.